Rape, Shame and Pride : Address to Stockholm Criminology Symposium, 16 June 2006 - Braithwaite, John (Journal of Scandinavian studies in criminology and crime prevention, 2006)
A proposition of the theory of reintegrative shaming is that a reason some societies have lower rates of rape is that rape is unthinkable to most men in those societies. This presentation shows how war interrupts the unthinkableness of rape. Bougainville society seems to have had a low level of rape until its war of the 1980s and 1990s. A single rape was one of the important sparks that lit its civil war. It caused perhaps over 5% of the population to lose their lives and perhaps over a third to be displaced from their homes. As in most wars, rape became common in Bougainville. A theory of why war causes epidemics of rape helps criminologists understand rape better. It can also help international relations scholars to see that the bigger problem caused by armed conflict today may be crime rather than battle deaths. Rape in peace and in war is interpreted according to Eliza Ahmed's theory of shame management and pride management. Ahmed's work is seen as an important advance in evidence-based criminological theory. A deficiency of reintegrative shaming theory is that it neglects pride as the flip side of shame as an emotion. Shame displacement may be important to the explanation of rape; yet narcissistic pride may be more important. In war we see more vividly the social dynamics of how shame displacement and narcissistic pride allow both rape and the onset of war itself. Bougainville helps us to ponder how historically sustained, deep and broad restorative justice processes may be part of what is needed to return a society to peace and to low levels of rape